Can lamina fresh mass be used to represent lamina dry mass? Evidence from Photinia serratifolia - Yan, Dan; Jiao, Yabing; Shi, Peijian (Frontiers in Ecology and Evolution, 2023)
Lamina dry mass (LDM) per unit area is an important plant functional trait. However, it is time-consuming to dry leaves in practice. Previous studies have demonstrated that lamina fresh mass (LFM) is approximately proportional to LDM for some broad-leaved plants. However, those studies largely overlooked the influence of leaf age on the proportional relationship, and leaves were sampled without distinguishing age. In the present study, we used eight leaf-age groups of Photinia serratifolia to test whether LDM is proportional to LFM. And we also compared the two linear equations (y = a + bx, and y = a + x, where x = log(LFM), y = log(LDM), a and b are constants to be estimated) to test whether the introduction of parameter b is worthwhile based on the percent error of the goodness-of-fit between the two equations. There were four of eight leaf-age groups whose 95% confidence intervals (CIs) for b included unity, and for the other four leaf-age groups the difference between the lower limit of the 95% CI and unity was smaller than 0.03, supporting the validity of the LDM vs. LFM proportional relationship. Additionally, the percent errors between the two equations for the eight leaf-age groups were all smaller than 5%, which further supports the hypothesis of a proportional relationship at the individual leaf-age group level. However, the LDM/LFM ratio exhibited a nonlinear (quadratic) function of time, which indicates that the intercept, a, depends upon leaf age.